Agreement on the use of land for the construction and operation of renewable energy installations – selected legal aspects - Jóźwiak, Jakub (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The paper presents an analysis of the legal nature of an agreement on the use of land for the construction and operation of renewable energy installations, especially wind farms. In particular, it focuses on the legal significance of the Supreme Court judgment of 5 October 2012 (IV CSK 244/12), which ruled that such an agreement cannot be regarded as a  lease. The author seeks to identify the possible practical consequences of this judgment and propose legislative measures to ensure the sustainability of such agreements, and thus the investments which go with them as well as to analyze the legal term fructus in the civil law in the context of this judgment.